(untitled) (The Research of Medical Science Review, 2024)
Introduction: The biocompatibility and long-term performance of dental materials are critical for their effectiveness in restorative and prosthetic dentistry. This study aims to evaluate various dental materials, composite resins, ceramics, metal alloys, and bioactive materials focusing on their cellular response and mechanical durability under conditions that simulate the oral environment. Objective: This study aims to assess the biocompatibility and long-term performance of selected dental materials to ensure safety and durability for clinical use. Method: A controlled laboratory study was designed to test commercially available dental materials commonly used in clinical settings. Sample preparation followed manufacturer instructions, with each material type represented by at least three brands. For biocompatibility testing, human oral fibroblasts and osteoblasts were cultured, and a cytotoxicity assay (MTT) quantified cell viability. Histological analysis was conducted to observe cellular morphology on the materials. Long-term performance testing included mechanical assessments (compressive strength, flexural strength, fracture toughness) following ISO standards, wear simulation via chewing cycles, and thermal cycling from 5°C to 55°C. Chemical degradation was tested through pH cycling in acidic and neutral environments, while ion release in metal-based materials was measured using ICP-MS. Data analysis included ANOVA and post-hoc testing, with p < 0.05 indicating statistical significance. Results: Biocompatibility varied across materials, with bioactive materials showing the highest cell viability and minimal cytotoxicity. Ceramics and composite resins exhibited excellent long-term stability, while some metal alloys showed higher ion release under acidic conditions. Mechanical testing confirmed high compressive and flexural strength in ceramics and certain composites, while thermal cycling showed material stability with minimal microcracking in high-performance ceramics. Conclusion: The study confirmed that dental materials, particularly ceramics and bioactive materials, offer high biocompatibility and long-term performance suitable for restorative applications. Results highlight the importance of material composition and surface treatments in enhancing both durability and cellular compatibility, guiding clinical material selection for improved patient outcomes..